Ortho-Effect of Reaction of Triethylammonium Ortho-Substituted Benzoates with Phenacyl Bromide - Krishna Pillay, M.; Sridharan, K. (Asian Journal of Chemistry, 2010)
The kinetics of the reaction of phenacyl bromide with ortho-substituted benzoic acids in the presence of triethylamine at 25º,30º and 35ºC in acetone have been studied. The reaction follows second order kinetics, first order with respect to phenacyl bromide and first order with respect to carboxylate. The attacking nucleophile is assumed to be triethylammonium benzoate ion-pair. Electronreleasing groups accelerate the reaction, while electron-withdrawing groups retard the reaction. The large negative entropy of activation indicates a rigid cyclic transition state. The existence of isokinetic relationship indicates that the same mechanism operates in the whole series. The rate data do not obey Bronsted relationship; the Taft's polar substituent constants and inductive effects of the ortho-substituents are found to be insignificant. The steric factors of the ortho-substituents are found to be less important while the resonance effect for this system is found to be more important in the reaction series.